2018
DOI: 10.1186/s12887-018-1096-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with congenital anomalies in Addis Ababa and the Amhara Region, Ethiopia: a case-control study

Abstract: BackgroundThe early stage of embryo development is extremely vulnerable to various teratogenic factors, leading to congenital anomalies. In Ethiopia, a significant number of babies are born with congenital anomalies, but the risk factors for the anomalies have never been studied. Understanding the specific risk factors for congenital anomalies is very essential to provide health education that aims at creating awareness and establishing preventive strategic plan/s. The main objective of this study was to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
48
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 56 publications
11
48
4
Order By: Relevance
“…Bianchi F et al also reported that the association between birth defects and being exposed to textile dye [25]. In agreement with our results, the authors reported that being exposed to chemicals during pregnancy played a significant role in having an infant with a major birth defect [13,29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Bianchi F et al also reported that the association between birth defects and being exposed to textile dye [25]. In agreement with our results, the authors reported that being exposed to chemicals during pregnancy played a significant role in having an infant with a major birth defect [13,29].…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of congenital malformation varies widely from country to country [2] and from region to region, with a range of 1.73 to 6.3% [12][13][14]. For example, it was reported to be 1.7% in Brazil [15], 2.22% in Eastern India [16], 3.63% in Iraq [17], 6.3% in Nigeria 6.3% [14].…”
mentioning
confidence: 99%
“…Unlike the present study where the NTDs were found to be the most prevalent defects, a study done in china indicated that septal defects (138.2 per 10,000) were the most prevalent followed by congenital hip dislocation (652 per 10,000) [26]. Unlike the presents, the study done in Addis Ababa and Amhara region by Mola et al, 2018 [19] revealed that were the most frequent the Oro-facial defects (34.2%) followed by Neural tube defects (30.8%).…”
Section: Discussioncontrasting
confidence: 63%
“…In the final review, articles were published from 10 countries among 46 countries were included. Of these studies, eleven studies were found from Ethiopia [13,19,[30][31][32][33][34][35][36][37][38], nine articles were from South Africa [20,22,[39][40][41][42][43][44][45][46], five articles were from Nigeria [18,[47][48][49][50], two studies were from Ghana [51,52], one article was from Kenya [53], three articles were from Tanzania [54][55][56], two studies were from Uganda [21,57] one study was from Burkina Faso [58], and one article was from Zambia [59]. Regarding the study designs, twenty-five (83%) of them were cross-sectional, three studies (3.5%) were cohort and three articles (3.5%) were case-control.…”
Section: Resultsmentioning
confidence: 99%